2018
DOI: 10.1016/j.celrep.2018.05.082
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Kill Antibody-Opsonized Cancer Cells by Trogoptosis

Abstract: Destruction of cancer cells by therapeutic antibodies occurs, at least in part, through antibody-dependent cellular cytotoxicity (ADCC), and this can be mediated by various Fc-receptor-expressing immune cells, including neutrophils. However, the mechanism(s) by which neutrophils kill antibody-opsonized cancer cells has not been established. Here, we demonstrate that neutrophils can exert a mode of destruction of cancer cells, which involves antibody-mediated trogocytosis by neutrophils. Intimately associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
391
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 292 publications
(411 citation statements)
references
References 69 publications
(95 reference statements)
19
391
1
Order By: Relevance
“…4E). Next, we were interested to analyze the mechanism of IgG2-mediated tumor cell killing by PMN, which was recently reported to be induced by trogocytosis (29). Incubation of PMN with DiO-membrane labeled A431 cells resulted in the uptake of tumor cell membranes by PMN in the presence of EGFR antibodies ( Fig.…”
Section: Egfr-directed Igg2 Antibodies Activate M1-like Macrophages Fmentioning
confidence: 99%
See 1 more Smart Citation
“…4E). Next, we were interested to analyze the mechanism of IgG2-mediated tumor cell killing by PMN, which was recently reported to be induced by trogocytosis (29). Incubation of PMN with DiO-membrane labeled A431 cells resulted in the uptake of tumor cell membranes by PMN in the presence of EGFR antibodies ( Fig.…”
Section: Egfr-directed Igg2 Antibodies Activate M1-like Macrophages Fmentioning
confidence: 99%
“…The transfer of membrane from tumor cells to neutrophils was measured by flow cytometry as described (29). Briefly, lamin-B-TRQ-transfected A431 cells were labeled at 37 C with the lipophilic membrane dye DiO (5 mmol/L, Invitrogen).…”
Section: Trogocytosis Assaymentioning
confidence: 99%
“…The previous paradigm was that microbes engage trogocytosis for cell-killing, but trogocytosis in multicellular organisms was believed to be a benign form of cell-cell interaction. However, recent reports have now shown that neutrophils can use trogocytosis to kill parasites [29], and that neutrophils and macrophages can use trogocytosis to kill cancer cells in a form of antibody-dependent cell-mediated cytotoxicity [30,31]. Trogocytosis is therefore likely to be a conserved, fundamental form of eukaryotic cell-cell interaction that can be cytotoxic or benign, depending on the context.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that neutrophils can detach and engulf fragments of Trichomonas vaginalis, using a process called trogocytosis [22][23][24][25] . Neutrophils can also kill cancer cells using trogocytosis 26 . The nibbling process of trogocytosis shows that neutrophils have the ability to remove small pieces from a large target before engulfing those pieces 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils can also kill cancer cells using trogocytosis 26 . The nibbling process of trogocytosis shows that neutrophils have the ability to remove small pieces from a large target before engulfing those pieces 26 . Phagocytosing Dictyostelium and Entamoeba can also break off and ingest small pieces of a target 27,28 .…”
Section: Introductionmentioning
confidence: 99%